FULLERENES AS AN EXAMPLE OF BIOMINERAL HOMOLOGY - Voytekhovsky Yu.L. (My University, 2003)
Fullerenes are widely applied in scientific and technical developments. Laboratory synthesis of them has led to such situation. Then, stable polyhedral carbon clusters, C60 and C70 have been found in natural substances. However, fullerene as form was earlier known in biology and geology. In connection with this, biomineral homology in formation of various structures has been considered. It has been shown that carbonic fullerenes form homological series. Homology has been noted among skeletons of Radiolaria. Circogonia icosahedra and Circogonia dodecahedra skeletons and viruses have also been considered.